TFII-I/Gtf2i and Erythro-Megakaryopoiesis - Gurumurthy, Aishwarya; Wu, Qiong; Nar, Rukiye; Paulsen, Kimberly; Trumbull, Alexis; Fishman, Ryan C.; Brand, Marjorie; Strouboulis, John; Qian, Zhijian; Bungert, Jörg (Frontiers in Physiology, 2020)
TFII-I is a ubiquitously expressed transcription factor that positively or negatively regulates gene expression. TFII-I has been implicated in neuronal and immunologic diseases as well as in thymic epithelial cancer. Williams Beuren Syndrome (WBS) is caused by a large hemizygous deletion on chromosome 7q11.23 which encompasses 26 to 28 genes, including GTF2I, the human gene encoding TFII-I. A subset of WBS patients has recently been shown to present with macrocytosis, a mild anemia characterized by enlarged erythrocytes. We conditionally deleted the TFII-I/Gtf2i gene in adult mice by tamoxifen induced Cre-recombination. Bone marrow cells revealed defects in erythro-megakaryopoiesis and an increase in expression of the adult β-globin gene. The data show that TFII-I acts as a repressor of β–globin gene transcription and that it is implicated in the differentiation of erythro-megakaryocytic cells.